The Impact of Obesity Assessed by Different Criteria on the Metabolic Parameters in Children and Adolescents in Georgia - Nino Tskhvedadze; Shota Janjgava; David Tananashvili; Elene Giorgadze (SAGE Publishing, 2022)
The aim of our study was comparative analysis of anthropometric characteristics in children and adolescents significantly correlated with the parameters of metabolic syndrome. The study group is consisted of 113 children and adolescents (study group) with excessive body weight and obesity (group 1-BMI percentile; group 2-waist circumference; group 3-waist to height ratio). The control group consisted of 113 children and adolescents without. Comparative analysis of obtained data have been carried out by multiple regression analysis. BMI percentile is more an indicator of a generalized obesity; WC and WHR percentiles better describe visceral obesity and metabolic disorders-insulin resistance, hypertension and dyslipidemia. However, the WHR Percentile may be a more useful tool. To assess obesity in children and adolescents, it is necessary to evaluate together BMI, WC, and WHR percentiles. It can be also concluded that these findings indicate the need to continue research in this direction.